2008
DOI: 10.1021/jp803481k
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum, Conformation and Intramolecular Hydrogen Bonding of 2,2,2-Trifluoroethanethiol (CF3CH2SH)

Abstract: The microwave spectrum of 2,2,2-trifluoroethanethiol, CF3CH2SH, and of one deuterated species, CF3CH2SD, has been investigated in the 7-80 GHz spectral interval. The microwave spectra of the ground and three vibrationally excited states belonging to three different normal modes of one conformer were assigned for the parent species, and the vibrational frequencies of these fundamentals were determined by relative intensity measurements. Only the ground vibrational state was assigned for the deuterated species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The present study also represents an extension of our recent investigations of the conformational properties of thiols such as 3-butyne-1-thiol (HSCH 2 CH 2 CtCH), 13 (Z)-3-mercapto-2propenenitrile (HSCHdCHCN), 14 cyclopropanethiol (C 3 H 5 -SH), 15 and 2,2,2-trifluoroethanethiol CF 3 CH 2 SH, 16 using MW spectroscopy augmented with quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 97%
“…The present study also represents an extension of our recent investigations of the conformational properties of thiols such as 3-butyne-1-thiol (HSCH 2 CH 2 CtCH), 13 (Z)-3-mercapto-2propenenitrile (HSCHdCHCN), 14 cyclopropanethiol (C 3 H 5 -SH), 15 and 2,2,2-trifluoroethanethiol CF 3 CH 2 SH, 16 using MW spectroscopy augmented with quantum chemical calculations.…”
Section: Introductionmentioning
confidence: 97%
“…Microwave (MW) spectroscopy has shown that the thiol group can form intramolecular hydrogen (H) bonds acting as a weak proton donor with a wide variety of acceptors. Examples include 2,2,2-trifluoroethanethiol (CF 3 CH 2 SH), trifluorothioacetic acid (CF 3 COSH), 1,2-ethanedithiol (HSCH 2 CH 2 SH), thiiranemethanethiol (C 2 H 3 SCH 2 SH), aminoethanethiol (H 2 NCH 2 CH 2 SH), methylthioglycolate (HSCH 2 COCH 3 ), propa-1,2-dienethiol (H 2 CCCHSH), 2-furanmethanethiol (C 4 H 3 OCH 2 SH), cyclopropanemethanethiol (C 3 H 5 CH 2 SH), propargyl mercaptan (HSCH 2 CCH), 2-propenethiol (H 2 CCHCH 2 SH), 3-mercaptopropionitrile (HSCH 2 CH 2 CN), 3-butene-1-thiol (HSCH 2 CH 2 CHCH 2 ), , 3-butyne-1-thiol (HSCH 2 CH 2 CCH), and ( Z )-3-mercapto-2-propenenitrile (HSCHCHCN) . The present investigation of mercaptoacetonitrile (HSCH 2 CN) is an extension of our longstanding interest in internal H bonding in general and in thiols in particular …”
Section: Introductionmentioning
confidence: 99%
“…Much of our work has focused on weak proton donor groups. Recently, we reported gas-phase studies of alcohols, carboxylic acids, thiols, thiolcarboxylic acids, selenols, amines, amides, , and phosphines, where the said groups are proton donors in internal H bonds with acceptors such as the fluorine atom, ,,, the chlorine atom, ,,, π-electrons of triple bonds, ,,,, π-electrons of double bonds, ,,,, and Walsh pseudo-π electrons. ,, References of many of our earlier works are found in the cited literature as well as in reviews. …”
Section: Introductionmentioning
confidence: 99%